Use of Communicative Strategies in L2 Learning: An Intercultural Study - Valverde Zambrana, José María (International Journal of English Studies, 2020)
Our objective is to describe the importance of the learning strategies, especially those of communicative type, in the learning of the second language. We made a comparative study of the use of L2 learning strategies by Spanish students at university and by students from international mobilities coming from the Erasmus+ programme and from The Republic of South Korea. In our study we also found that gender was a significant factor among all students regardless their nationalities. We found that the female students made a greater use and with more frequency of all type of learning strategies, especially those of communicative type, with special relevance in the socio-affective strategies. In our conclusion, we indicate that education or qualification in the strategies of learning for the acquisition of a language can help the student of a foreign language to learn better if his/her awareness of the learning strategies is increased, and if the number of strategies that the students use is enlarged.